The Failure of Providing Human Security For Rohingya Refugees (Case Study: Escaping Rohingya Refugees From Shelter In Skb Bireuen, Aceh Province) - Risky Novialdi (Indonesian Journal of Peace and Security Studies (IJPSS), 2020)
This paper analyses the failure to provide humanitarian security for Rohingya refugees at the Sanggar Kegiatan Bersama (SKB) in Bireuen, Aceh. Humanitarian protection should provide security and comfort for Rohingya refugees. However, according to a local newspaper 'Serambi', on 15 February 2019 there were only 11 Rohingya refugees living in the Bireuen SKB. This number increased to 79 people on 20 April 2019. This means that Aceh has failed to provide human security for Rohingya refugees. What exactly caused this failure? While Aceh has provided human security in a political context, it has been unable to provide human security in an economic sense. In addition, there have been allegations that Rohingya refugees in Aceh are not only seeking asylum but also trying to find work. From initial observation until 15 April 2019, only two people were still living in the SKB as refugees. The other refugees had escaped from the shelter. This paper draws on interviews and direct observation at the Bireuen SKB.